Bilingual Analysis in Early Childhood: A Meta-Analysis Study - Na'imah Na'imah (Pendidikan Bahasa Inggris Universitas Nurul Huda, 2022)
Mastery of foreign languages is an added value in life. Bilingualism is the focus of attention for researchers and educators. The ability to speak foreign languages is a challenge for alpha generation children to communicate and collaborate with other people both domestically and internationally. Especially in the golden age when children are susceptible to the stimuli and stimuli given. This article aims to increase understanding of how the bilingual effect can play a role and affect early childhood. This article is a qualitative research study to make a phenomenon or fact easier to understand and produce a hypothesis. Recently used document studies with Crossref Data Search, Google Scholar, Taylor & Francis, and Harzing's Publish or Perish software. Google This study aims to describe previous research on bilingualism and its relation to early childhood. Changes that occur in society also change language learning and teaching. Language is valued as an important part of social processes and interactions. This point of view has prompted various studies to focus on language learning. This study has presented findings and recommendations to help other researchers and language educators suggest new methods and findings on how to learn bilingually in early childhood. For the next expected study, there is data that discusses parents' hope for bilingualism practiced in children age early with the reality that happens at school.